Consumer Acceptance Testing of Nipa (Nypa fruiticans) Marmalade Filled Roll (NMFR) for Product Development - Perlita R. Israel (Research Synergy Foundation, 2022)
This research will lead to commercializing the technology generated by the Aklan State University (ASU) - Ibajay, Aklan, Philippines. The investigation aims to find the consumers’ acceptance of the nipa (Nypa fruiticants) marmalade-filled roll for product development. The descriptive method was employed in the study. The data was gathered from the participants of the Regional Science and Technology Week (RSTW) at the Iloilo Convention Center (ICON), Iloilo City, Philippines. The 150 tasters were selected through purposive sampling. Based on the results, the tasters represent various age groups, gender, and occupations. The sensory testing revealed that the product was liked very much by tasters in terms of appearance, flavor, texture, aroma, and overall acceptability. The tasters had a positive first reaction to the product and rated its innovativeness as “very innovative”. Similarly, the tasters disclosed that “very likely” they will buy the product if it is available for sale and will tend to recommend it to their colleagues. Moreover, the results further revealed that the gender of the tasters and their tendency to buy the product has a significant correlation. Consequently, occupation and innovativeness, and occupation and tendency to recommend the product were found to have significant correlations, respectively. Likewise, the taste of the product satisfied the tasters. However, the tasters revealed that packaging should be improved. Further study along with this, specifically on shelf life and proximate analysis, is recommended before bringing the product to a bigger market.